Whole‐genome analysis of multiple wood ant population pairs supports similar speciation histories, but different degrees of gene flow, across their European ranges - Beatriz Portinha; Amaury Avril; Christian Bernasconi; Heikki Helanterä; Josie Monaghan; Bernhard Seifert; Vitor C. Sousa; Jonna Kulmuni; Pierre Nouhaud (Molecular Ecology, 2022)
The application of demographic history modelling and inference to the study of divergence between species has become a cornerstone of speciation genomics. Speciation histories are usually reconstructed by analysing single populations from each species, assuming that the inferred population history represents the actual speciation history. However, this assumption may not be met when species diverge with gene flow, for example, when secondary contact may be confined to specific geographic regions. Here, we tested whether divergence histories inferred from heterospecific populations may vary depending on their geographic locations, using the two wood ant species Formica polyctena and F. aquilonia . We performed whole‐genome resequencing of 20 individuals sampled in multiple locations across the European ranges of both species. Then, we reconstructed the histories of distinct heterospecific population pairs using a coalescent‐based approach. Our analyses always supported a scenario of divergence with gene flow, suggesting that divergence started in the Pleistocene (c. 500 kya) and occurred with continuous asymmetrical gene flow from F. aquilonia to F. polyctena until a recent time, when migration became negligible (2–19 kya). However, we found support for contemporary gene flow in a sympatric pair from Finland, where the species hybridise, but no signature of recent bidirectional gene flow elsewhere. Overall, our results suggest that divergence histories reconstructed from a few individuals may be applicable at the species level. Nonetheless, the geographical context of populations chosen to represent their species should be taken into account, as it may affect estimates of migration rates between species when gene flow is spatially heterogeneous.